SINTESIS DAN TRANSISI ELEKTRONIK KOMPLEKS TEMBAGA (II)-KLOROFIL - Imelda Hotmarisi Silalahi; Julan Julan; Muhammad Yusprianto; Rudiyansyah Rudiyansyah (Indonesian Journal of Pure and Applied Chemistry, 2020)
The copper (II)-chlorophyll complex was prepared from the reaction between the chlorophyll isolated from cassava leaves and the metal ion precursor, CuSO4.5H2O in methanol under reflux for four hours. The FTIR spectra of the reaction product compared to the chlorophyll spectra show an indication of a complexation through metal coordination with the N atom from the phyrol ring replacing the magnesium (II) ion in chlorophyll.This assumption is drawn based on changes on FTIR spectra, i.e. vibration absorption originating from the CN and NH groups in the porphyrin ring and the appearance of the distinctive vibration band of nitrogen-metal bonds which is annotated as Cu-N groups at 599.88 cm-1. Another sign is the change in the OH and CO vibration bands which imply changes in aggregate properties that occur through inter-molecular interactions due to the introduction of copper (II) metal into the chlorophyll structure. The formation of copper (II)-chlorophyll compounds is also shown from the results of atomic absorption spectroscopy by recording copper metal in the product and reducing magnesium metal concentration. UV-vis spectra of chlorophyll in methanol show a characteristic band in the dark area (Soret band) at a maximum wavelength of 404 nm and the visible area (Q band) with the strongest intensity at 665 nm. These peaks appear to shift hypsochromically in the copper (II)-chlorophyll compound to 397 nm and 650 nm with higher absorptivity, indicating a change in the electronic transition of the chlorophyll after coordinating with the copper (II) ion. A new peak at 411 nm was also observed which is suggested to indicate that the copper (II) -chlorophyll complex is in an octahedral geometry in the aggregate coordinated via nitrogen atoms in the phyrol ring in place of the magnesium (II) ion.